Effectiveness of insulin tea on hyperglycemia levels in climacterium age women - Na`ilul Latifah; Diah Atmarina Yuliani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Indonesia has 284.4 million people, including 54.2 million women over 40 years. In Baturraden District, 9,356 women fall within this age group, entering the climacteric phase (ages 40–65). This transitional stage, marked by declining estrogen and progesterone, cessation of menstruation, and symptoms such as hot flushes, sleep disturbances, and mood changes, increases vulnerability to degenerative diseases, notably diabetes mellitus characterized by hyperglycemia. Purpose: To determine the effectiveness of insulin tea administration on hyperglycemia levels in women in climacterium age. Method: A quantitative study was employed through a case control approach with unpaired numerical comparative analysis in two groups with one measurement. With 31 participants in the treatment and control groups. Results: There was a difference in results between before and after being given insulin tea for 7 days with an average difference of 86.39 mg/dL with a p value = <0.001. Conclusion: Insulin tea administration is effective in controlling hyperglycemia levels. Suggestion: This research is expected to be the foundation in efforts to use insulin plants, so that it can become a legal product and can be used by the community easily.